2016
DOI: 10.1186/s12906-016-1053-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticancer properties of a decoction containing Adenanthera pavonina L. and Thespesia populnea L.

Abstract: BackgroundA decoction composed of Adenanthera pavonina L. and Thespesia populnea L. is currently being used in the treatment of cancer patients.MethodsLactate Dehydrogenase (LDH) release, (3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) MTT, and Sulforhodamine B (SRB) assays were carried out to study cytotoxicity and anti-proliferative activity against the HEp-2 cells, 24 h post-treatment with the decoction.ResultsThe mean (± SD) values of EC50 were 195.50 (±40.68), 120.02 (±29.82) and 77.06 (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…On the other hand, the ethanol extract showed low growth inhibition against all the cancer cell lines. Lindamulage and Soysa (2016) observed that a decoction prepared with barks of A. pavonina and Thespesia populnea in equal proportion, exhibited antiproliferative activity and induced apoptosis in the Hep-2 cancer cells, 24 h post-treatment. Araujo et al (2019) evaluated the influence of antiproliferative activity against cancer cells of A. panonina seed powder treated enzymatically with amylase, cellulase, and protease.…”
Section: Anticancer Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the ethanol extract showed low growth inhibition against all the cancer cell lines. Lindamulage and Soysa (2016) observed that a decoction prepared with barks of A. pavonina and Thespesia populnea in equal proportion, exhibited antiproliferative activity and induced apoptosis in the Hep-2 cancer cells, 24 h post-treatment. Araujo et al (2019) evaluated the influence of antiproliferative activity against cancer cells of A. panonina seed powder treated enzymatically with amylase, cellulase, and protease.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…According to the literature, this plant was used in ancient Indian medicine, where crushed seeds were used to treat boils and inflammations (Olajide et al, 2004). In general, the literature reports its empirical use for diabetes, lipid disorders, diarrhea, ulcers, stomach bleeding, hematuria, rheumatism, asthma, hypertension, pulmonary infections and chronic ophthalmia (Pandhare et al, 2012a;Zeid et al, 2012;Mujahid et al, 2013;Godoi et al, 2014;Moniruzzaman et al, 2015;Dissanayake et al, 2018) and cancer (Lindamulage and Soysa, 2016). Zeid et al (2012) reported its use as a tonic.…”
Section: Ethnomedicinal Usementioning
confidence: 99%
See 1 more Smart Citation
“…Sus resultados se interpretan dependiendo del contexto en que se plantea el objetivo de la investigación, si la sustancia evaluada no es citotóxica es un indicador que esta sustancia puede ser bien tolerada por un sistema biológico, y si la sustancia es citotóxica es un indicador que esta sustancia puede contener compuestos bioactivos con potencial efecto antitumoral (9) . Es importante señalar que un estudio desarrollado por el National Cancer Institute de los Estados Unidos mostró que existe una fuerte correlación entre la prueba de letalidad de Artemia salina, y la inhibición del crecimiento in vitro en líneas celulares de tumores sólidos humanos (10) ; estos resultados han servido para que, actualmente, varios estudios utilicen esta prueba para establecer un mecanismo de selección preliminar de especies vegetales con potencial anticancerígeno (11,12) .…”
Section: Introductionunclassified
“…Up to now, Africa still provides a non-negligible contribution to overall complementary and alternative medicines despite the fact that traditional medical practitioners have been using crude drug extracts for several years [ 1 4 ]. Thus, there is rationale in investigating herbal toxicity within the African health care system [ 5 , 6 ], given that a sizable part of our population regularly use them.…”
Section: Introductionmentioning
confidence: 99%